Pengaruh Faktor Sosial Ekonomi dan Lingkungan Terhadap Prevalensi Demam Berdarah Dengue di Wilayah Kerja Puskesmas Sangurara, Bulili dan Birobuli Kota Palu - M. Guli, Musjaya; Nita; Yuniati, Eny; Ardiputra, Muh.Akbar; Toemon, Agnes Immanuela (Fakultas Kedokteran, Universitas Palangka Raya, 2024)
Dengue fever is one of the diseases that is still a problem in Indonesia. The incidence of DHF cases in Central Sulawesi, especially Palu City, has increased every year. Environmental and socio-economic factors affect the breeding of Aedes Aegypti mosquitoes. This study aims to determine the effect of socio[1]economic and environmental conditions on the incidence of DHF in the working areas of Sangurara, Bulili and Birobuli health centers in Palu City, Central Sulawesi. The method used quantitative with cross sectional research design. Sampling using Simple Random Sampling technique. The number of samples was 51 cases and 51 controls. Analysis technique used Chi- Square. From the results of the study, the variables that significantly influenced the incidence of DHF were education (p-value = 0.012), occupation (p-value = 1.000), income (p-value = 0.029), frequency of draining containers (p-value = 0.008), habit of hanging clothes (p-value = 0.031), home environment conditions (p-value = 0.005). While the variables that did not affect the incidence of DHF were the availability of lids on containers (p-value = 1.000), and the presence of larvae in containers (p-value = 0.127). This study concluded that education, income, frequency of container draining, habit of hanging clothes and home environmental conditions had a significant influence on the incidence of DHF and there was no influence between occupation, availability of container lids and the presence of larvae in containers.